Modern public economics - Jha, Raghbendra (London, 1998)
Modern Public Economics covers all aspects of state intervention in the marketplace. Part 1 is a detailed study of classical theories of welfare economics and also explains key concepts in consumer demand theory. Part II analyses the theory of public expenditure, paying particular atten tion to pure public goods. Part III is an extremely detailed account of the theory of taxation. Subjects covered include the incentive effects of taxation on labour supply, investment and risk-taking; static and dynamic tax incid ence; commodity taxation; optimal income taxation and tax reform. Part IV assesses applied problems in public economics and deals with issues such as public sector pricing, international taxation and cost-benefit analysis. Part V deals with key issues in fiscal federalism.
Keywords: Economics